SP10.1.4 Association between public holidays and acute admission with biliary colic: a retrospective analysis. (9th August 2022) - Dick, Lachlan; Young, Jamie
Abstract: Introduction: Biliary colic symptoms are often post-prandial, particularly following fatty foods. Public holidays and festive periods are frequently celebrated using such foods. We aimed to determine the rates of admission following public holidays at a Scottish district general hospital. Methods: Emergency admissions with biliary colic from June 2016 to June 2019 were included. Public holiday dates were extracted from the Scottish government website. To include those with delayed presentation, the 3-days following a public holiday were also considered to be public holiday-related (PHR). Statistical analysis was performed to determine any differences in demographics or outcome. Results: Of the 273 patients included, 1 (0.4%) was admitted on a public holiday with a further 27 (9.9%) admitted on a PHR day. PHR days accounted for 104 (9.2%) of the 1125 days included in the study. Comparing those admitted on a PHR and non-PHR day, there was no difference in age (61.6 vs 61.1 years, p=0.895), female gender (75 vs 66.5%, p=0.365), length of stay (6 vs 4 days, p=0.250) or operative intervention (53.5 vs 37.6%, p=0.09). Conclusion: The majority of PHR admissions with biliary colic occur during the 3-days following a public holiday. It is therefore likely that the need for radiological investigation and access to emergency theatre will be greater during this period. Future work could assess the impact of other cultural holidays which are not reflected in public holidays.